2016
DOI: 10.4238/gmr.15028046
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between methylation of the E-Cadherin gene and malignancy of prostate cancer

Abstract: ABSTRACT. Prostate cancer is a common malignant tumor in males with an unclear pathogenic mechanism. As one epigenetic regulation mechanism, DNA methylation of the whole genome and specific gene(s) plays critical roles in pathogenesis, progression, diagnosis, and treatment of prostate cancer. The E-Cadherin gene is involved in cell metabolism and has been suggested to be related with malignancy of multiple tumors. This study investigated the correlation between E-Cadherin methylation and malignancy of prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…29 Our previous study observed that polyphenols affect the bioavailability of carotenoids. 18 In this study, LUT contents were detected in the liver and feces of mice. As shown in Fig.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…29 Our previous study observed that polyphenols affect the bioavailability of carotenoids. 18 In this study, LUT contents were detected in the liver and feces of mice. As shown in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…The gavage dose of LUT was set at 100 mg per kg (BW per day), 16 the gavage dose of EGCG was set at 500 mg per kg (BW per day), and the ratio between LUT and EGCG was referred from the previous study. 18 LUT was dissolved in soybean oil, and EGCG was dissolved in water to prepare the corresponding concentration solution. The quality of LUT in the LUT-EGCG group is equivalent to that in the LUT and EGCG groups alone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human PC, E-cadherin downregulation is frequent in later stages of the disease and poorly differentiated tumors (Ipekci et al, 2015; Zhang et al, 2016a). Considering the dynamic process of E -cadherin expression, a group of cases with negative cells could also be associated with worse prognosis in canine PC.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is an important characteristic of human malignant tumors; decreased E‐cadherin and increased vimentin levels are characteristic of the EMT progression in various human cancers, including PC (X. Li et al, ). Previous studies showed that E‐cadherin interacts with various extracellular and intracellular proteins, and its decreased expression is closely related to metastasis (Zhang, Zhang, & Zhang, ). Increased expression of vimentin is observed during metastasis of many human tumors such as breast cancer and PC (Chaw et al, ; Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%